Obstructive Jaundice Caused by Clonorchiasis-associated Duodenal Papillitis: A Case Report - Lim, Jun Uk; Joo, Kwang Ro; Shin, Hyun Phil; Cha, Jae Myung; Lee, Joung Il; Lim, Sung Jig (Journal of Korean medical science, 2011)
We describe an unusual presentation of Clonorchis sinensis infection with obstructive jaundice due to duodenal papillitis which was relieved dramatically by endoscopic sphincterotomy. A 26-yr-old male presented with complaints of fatigue, weight loss and painless jaundice. The history was significant for frequent ingestion of raw freshwater fish. The patient underwent endoscopic retrograde cholangiopancreatography for evaluation of obstructive jaundice. The duodenal papilla was markedly edematous with a bulging configuration and hyperemic changes at the orifice. Cholangiography revealed mild bile duct dilatation and irregular wall changes with multiple indentations. However, there were no biliary stricture or stones noted as the cause of obstructive jaundice. We performed an endoscopic sphincterotomy for effective bile drainage through the duodenal papilla. After the sphincterotomy, the patient's jaundice was dramatically improved. Pathology of the duodenal papilla showed eosinophilic infiltration of the mucosa. Parasitic eggs, consistent with the diagnosis of C. sinensis, were found in the bile sample.